Field notes contributed by Robert K. Myers, spring 1982 - Myers, Robert K.et al (1982)
Field notes were contributed by Robert K. Myers and other observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1982. Epson - sheet feed